The Role Of Research And Development (R&D) On Gross Domestics Products (GDP) (Case Study USA, China, Japan, Germany and UK) - Khoirudin, Rifki (Journal of International Conference Proceedings, 2023)
Research and Development (R&D) is an activity that is considered to be able to increase the country's productivity. R&D activities can produce the latest technological findings supporting the output production process. This research uses the USA, China, Japan, Germany, and the UK as research objects or case studies with 1996-2018 observation years. These five countries are developed countries and are the top five countries with the highest nominal GDP in the world. The main objective of this study is to examine the role of R&D in economic growth as measured by GDP. The dependent variable in this study is economic growth (GDP). In contrast, the independent variables include the ratio of R&D spending to GDP, the number of patents, the number of workers, the ratio of foreign direct investment to GDP, and total factor productivity. By using the standard effect model, this study confirms that all independent variables simultaneously have a positive and significant effect on economic growth in the five countries that are the research object. As for partially, the ratio of R&D expenditure to GDP and the number of patents does not have a positive and significant effect on economic growth.